Kontribusi Bakat Mekanik dan Proses Belajar pada Mata Pelajaran Produktif terhadap Kompetensi serta Kesiapan untuk Bekerja di Industri - Maryani, Penny (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2012)
The research was motivated by the many indications of the students do not have mechanical aptitude, so have difficulty in following the process of learning in productive subjects for both theory and practice during the learning process less motivated, the number of students who are not competent and did not pass the competency test and should carry out remedial and percentage SMK Vijayakusuma graduate students working in the industry in accordance with the competence and expertise is very small. The purpose of this study was to determine the contribution mechanical talents, the learning process in productive subjects and competence to work in the industry. This study took a sample of 80 students. Method is a descriptive correlational study with data processing using path analysis. Research results are Mechanical talents, the process of learning in productive subjects and competence together make a positive contribution to the readiness to work in the industry at 56.5%. The conclusion from this study that partial mechanical aptitude, the learning process in productive subjects contribute to the readiness and competence to work in the industry is at a low level.